Pharmacokinetics of orally administered ABT-751 in children with neuroblastoma and other solid tumors - Fox, Elizabeth (Cancer Chemother Pharmacol, 2010)
PURPOSE: To describe the pharmacokinetics of orally administered ABT-751 and its conjugated metabolites in children with neuroblastoma and other solid tumors and to relate pharmacokinetic parameters to toxicity and therapeutic outcomes. METHODS: Patients (median age, 11 years) with neuroblastoma (n = 37) or other solid tumors (n = 25) had pharmacokinetic sampling after the first dose of ABT-751 (75–250 mg/m(2)/day) on a 7-day or 21-day schedule. ABT-751 and its glucuronide and sulfate metabolites were quantified with an HPLC/MS/MS assay. Pharmacokinetic parameters were derived with non-compartmental methods. The relative bioavailability of more water soluble capsule and suspension formulations was assessed. RESULTS: ABT-751 peaked in plasma at 2 h and declined monoexponentially with a t(1/2) of 5.1 h. The apparent clearance was 33 ml/min/m(2) and was age-independent. The AUC(0–∞) increased in proportion to the dose, and at 200 mg/m(2) the median AUC(0–∞) was 91 mcg h/ml and the C(ave) was 3.9 mcg/ml. Inter-and intra-patient variability was low. The metabolites were detected in plasma 30 min post-dose and peaked 3–5 h after the dose. The glucuronide:sulfate molar AUC(0–∞) ratio was 0.57. Less than 1% of the dose was excreted in urine as parent drug; 13% of the dose was excreted as sulfate metabolite and 10% as glucuronide metabolite. The relative bioavailability of the water soluble capsule and suspension formulations was 105 and 93%, respectively. AUC(0–∞) was higher in patients experiencing dose-limiting toxicity. CONCLUSIONS: Oral ABT-751 pharmacokinetics was dose-proportional and age-independent with minimal intra- and inter-patient variability in children.